Efektivitas Ekstrak Serai Wangi (Cymbopogon nardus) sebagai Insektisida Nabati untuk Pengendalian Larva Crocidolomia pavonana Zell. pada Tanaman Kubis (JURNAL ENFIT : Entomologi dan Fitopatologi, 2020)
One of the pests that attack cabbage plants is Crocidolomia pavonana Zell. As an agrarian country, Indonesia has various types of plants that can be used as plant-based insecticides. Fragrant lemongrass plants (Cymbopogon nardus) is one type of plant that can be used as a vegetable insecticide. This study aims to analyze the mortality of C. Pavonana larvae. and know the effectiveness of C. nardus extract in controlling C. Pavonana larvae. . The research was conducted at the Center for the Protection and Testing of Food Crops and Horticulture in North Sulawesi Province, for 6 (six) months from November to May 2019.Â  Using a Completely Randomized Design (CRD) with 5 treatments and 4 replications and 1 control as a comparison. The research process includes preparation of tools and materials, propagation of test insects, planting cabbage as feed, extraction processes and so on. The results showed that C. nardus extract was effective in controlling C. Pavonana larvae. The highest percentage of mortality (mortality) was at a treatment concentration of 40% with a mortality rate of 93,3% on the third day of observation. analysis of variance shows that the use of fragrant lemongrass (C. nardus) has a very significant effect on mortality of C. pavonana larvae.